(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This article describes a triple band monopole antenna. t has been assumed that the WiMAX band application is objective. In order to attain the required band, various iterations of the proposed antenna design are carried out. The proposed antenna in the shape of broken hearts operates in the frequency range of 3.2GHz to 4.1GHz. In the final iteration, the heart-shaped double slotted ring resonator (SRR) with two different radii is seen to improve the bandwidth (900MHz) and gain (3dB). In this design, additional parameters like VSWR (approximately 2 at the WiMAX band), impedance (real and imaginary), and efficiency (approximately 89%) have been observed. As a result, the proposed monopole antenna in the shape of a broken heart that operates in the WiMAX band exhibits high efficiency, reduced size, and moderate gain. which play a crucial role in the WIMAX application band.